New Insight Into the Interspecies Shift of Anammox Bacteria Ca. “Brocadia” and Ca. “Jettenia” in Reactors Fed With Formate and Folate - Kallistova, Anna; Nikolaev, Yury; Grachev, Vladimir; Beletsky, Alexey; Gruzdev, Evgeny; Kadnikov, Vitaly; Dorofeev, Alexander; Berestovskaya, Julia; Pelevina, Anna; Zekker, Ivar; Ravin, Nikolai; Pimenov, Nikolai; et al. (Frontiers in Microbiology, 2022)
The sensitivity of anammox bacteria to environmental fluctuations is a frequent cause of reactor malfunctions. It was hypothesized that the addition of formate and folate would have a stimulating effect on anammox bacteria, which in turn would lead to the stability of the anammox process under conditions of sharp increase in ammonium load, i.e., helps overcome a stress factor. The effect of formate and folate was investigated using a setup consisting of 3 parallel sequencing batch reactors equipped with a carrier. Two runs of the reactors were performed. The composition of the microbial community was studied by the 16S rRNA gene profiling and metagenomic analysis. Among anammox bacteria, Ca. “Brocadia” spp. dominated during the first run. A stimulatory effect of folate on daily nitrogen removal rate (dN) was identified. The addition of formate led to progress in dissimilatory nitrate reduction and stimulated the growth of Ca. “Jettenia” spp. Spatial separation of two anammox species was observed in the formate reactor: Ca. “Brocadia” occupied the carrier, and Ca. “Jettenia” - the walls of the reactors. Biomass storage at low temperature without feeding led to an interspecies shift in anammox bacteria in favor of Ca. “Jettenia”. During the second run, a domination of Ca. “Jettenia” spp. was recorded along with a stimulating effect of formate and no effect of folate on dN. Comparative genome analysis revealed the patterns suggesting different strategies used by Ca. “Brocadia” and Ca. “Jettenia” spp. to cope with environmental changes.